THE KEY ASPECTS OF MODERNIZATION OF RUSSIAN ECONOMY - Oleg Vasilievich Chabanuk (Science and Innovation Center Publishing House, 2015)
The essence of methodology of modernization of the Russian economy is considered. Possible models and economic factors of innovative development of Russia are considered. The complex of problems of modernization of the Russian economy. Examined and classified the key constraints to economic growth in Russia.